Design, synthesis, and identification of silicon incorporated oxazolidinone antibiotics with improved brain exposure - Seetharamsingh, B.; Ramesh, Remya; Dange, Santoshkumar S.; Khairnar, Pankaj V.; Singhal, Smita; Upadhyay, Dilip; Veeraraghavan, Sridhar; Viswanadha, Srikant; Vakkalanka, Swaroop; Reddy, D. Srinivasa (ACS Medicinal Chemistry Letters, 2015)
Therapeutic options for brain infections caused by pathogens with a reduced sensitivity to drugs are limited. Recent reports on the potential use of linezolid in treating brain infections prompted us to design novel compounds around this scaffold. Herein, we describe the design and synthesis of various oxazolidinone antibiotics with the incorporation of silicon. Our findings in preclinical species suggest that silicon incorporation is highly useful in improving brain exposures. Interestingly, three compounds from this series demonstrated up to a 30-fold higher brain/plasma ratio when compared to linezolid thereby indicating their therapeutic potential in brain associated disorders.
Keywords: Antibacterial; brain exposure; linezolid; oxazolidinone; sila analogue

Determination of the absolute configuration of gliomasolide D through total syntheses of the C-17 epimers - Seetharamsingh, B.; Ganesh, Routholla; Reddy, D. Srinivasa (Journal of Natural Products, 2017)
The absolute configuration at C-17, the carbon bearing the distal hydroxy group of the 14-membered natural product gliomasolide D, was assigned as R by comparison of C-13 NMR shifts and specific rotation values of the epimers at C-17. The first total synthesis of gliomasolide D along with its C-17 epimer, regioselective macrocyclization (18 membered vs 14 membered), and regioselective Wacker oxidation are highlights of the present work.